"Water in the desert?" : Oil India’s CSR impact in Assam - Chaudhri, Vidhi; Kaul, Asha (London : Indian Institute of Management, Ahmedabad, 2024)
Incorporated on February 18, 1959, Oil India Ltd. (OIL) is a leading public sector oil and gas company. The company has interests in the exploration, development, production and transportation of crude oil and natural gas in India. Since its inception, OIL has committed itself to being a socially responsible organisation in and around operational areas, particularly the northeastern state of Assam, where 90% of its operations are concentrated. Despite many successes, the "People's Company" continues to be a target for disgruntled local and student communities who frequently create operational hazards for the company—from sit-ins and blockades to pilfering and disrupting production facilities. No less than 400 organisations, of which 50–60 are consistently active, are currently at the forefront of demanding something from OIL. Many of these demands are beyond the purview of OIL's corporate social responsibility (CSR) policy and focus areas. Additionally, being a public sector undertaking (PSU), it faces multiple disconcerting demands from the government.On February 16, 2019, Utpal Bora (chairman and managing director, OIL) and Biswajit Roy (director, Human Resources & Business Development, OIL) received news of yet another blockade in Duliajan, Assam. Members of several student unions supported by some local residents had combined forces to block employees' entry to OIL premises in Duliajan. Their actions were allegedly provoked by the lack of response to their demand for OIL to construct a road. Roy's mind, besieged with recent events and conflicting emotions, carried the heavy weight of a single question: What steps should OIL take to address and possibly mitigate operational interruptions?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Oil industries -- India -- Case studies; Gas industry -- India -- Case studies; Social responsibility of business -- India -- Case studies